Simultaneous total occlusion of two coronary arteries associated with use of drospirenone-ethinyl estradiol (oral contraceptive) - Hüsnü Atmaca; Diyar Köprülü; Tuncay Kiriş; Gönül Zeren; İrfan Şahin (KARE Publishing, 2018)
Although the use of oral contraceptives is associated with an increased risk of venous thromboembolic disease, the risk of myocardial infarction (MI) is unclear. A new, third-generation contraceptive agent, drospirenone-ethinyl estradiol, which contains less estrogen and a new progestogen, drospirenone, in a different combination, has been considered more reliable in terms of risk of MI. However, there have been some cases of MI associated with the use of drospirenone-ethinyl estradiol, despite the protective effects of this oral contraceptive. In this report, a 33-year-old woman who had used drospirenone-ethinyl estradiol for 6 months was admitted with MI and symptoms of cardiogenic shock. Coronary angiography revealed the total occlusion of 2 coronary arteries and so percutaneous coronary intervention was performed. To the best of our knowledge, this is the first case report of simultaneous total occlusion of 2 coronary arteries associated with the use of drospirenone-ethinyl estradiol in the English-language medical literature.